Phytochemical Investigation and Screening of Antibacterial Activity of Extracts from Leaves of Eupatorium odoratum Linn. - Sankar Nayak, Bhabani; Mishra, Debidani; Sankar Pradhan, Bhavani; Upadhaya, Dheerendra; Ellaiah, P.; Ramakrishna, S. (Asian Journal of Chemistry, 2012)
Eupatorium odoratum Linn. is found in the tribal area of Koraput district and extensively used traditionally by the tribal people as anthelmintic, antibacterial, antifungal and wound healing agent. The present study is an attempt to preliminary investigation of phyto-chemical constituents and to explore the antibacterial activity of different extracts of leaves of plant Eupatorium odoratum using petroleum ether, ethanol and chloroform as solvents. Various doses of extracts were screened for phytochemical constituent and evaluated for their antibacterial activities on human pathogens like Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Salmonela typhi. Tests for alkaloids and tannins were positive for all extracts. Tests for saponins, proteins, amino acids and anthraquinones glycoside were negative for all extracts. All extracts showed antibacterial activity at 2 mg/mL concentration. The activities are compared with the chloramphenicol. All the doses of petroleum ether, ethanol and chloroform extracts of Eupatorium odoratum showed lesser antibacterial activity than the standard drug. When the dose of the extract is increased, a gradual increase in antibacterial activity was observed. The petroleum ether and chloroform extracts exhibited weak antibacterial activity. The ethanol extract showed good inhibitory action against all the tested microorganisms, as compared to the other two extract. The data verified as statistically significant by using one way ANOVA at 5 % level of significance (p < 0.05).